1979
DOI: 10.2135/cropsci1979.0011183x001900060019x
|View full text |Cite
|
Sign up to set email alerts
|

Root Characteristics of Black Beans. I. Relationship of Root Size to Lodging and Seed Yield1

Abstract: The relationship of root size to seed yield and lodging of two black bean (Phaseolus vulgaris L.) cultivars, ‘Black Turtle Soup’ (BTS) and ‘Strain 39,’ was compared with that of four black‐seeded lines (70001, 70002, 70003, and 70004) under both field and greenhouse conditions at different growth stages. Root weight was significantly higher for the four lines than for the two cultivars in the field, but not in the greenhouse. Shoot:root ratios were significantly lower for all the lines than for BTS in both env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This suggests that high temperatures may have limited root growth in plants transplanted to the top of the rootball. Stoffella et al (1979) and Kahn (1985) observed that vegetable plants with greater root weights were less likely to lodge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that high temperatures may have limited root growth in plants transplanted to the top of the rootball. Stoffella et al (1979) and Kahn (1985) observed that vegetable plants with greater root weights were less likely to lodge.…”
Section: Resultsmentioning
confidence: 99%
“…Optimum temperatures for root growth can vary among plant species. Fluctuations of soil temperatures outside the optimum range can restrict root growth (McMichael and Burke, 1998;Stoffella et al, 1979).…”
mentioning
confidence: 99%
“…Providing uniform moisture levels around the hypocotyl during the last 2 weeks before field establishment is also thought to enhance basal root primordia development in transplants. The importance of basal root development in the field has been emphasized in peppers (Leskovar and Cantliffe, 1993), black beans (Stoffella et al, 1979a), and tomatoes (Zobel, 1975).…”
Section: Establishment Methods: Effect On Root Developmentmentioning
confidence: 99%
“…Reviews of genotypic variation in root morphological characteristics and variation in root system phenotypes have been reported by O' Toole and Bland (1987), and of rhizogenetic variation in vegetable crops by Zobel (1975Zobel ( , 1986. Root morphological traits can be directly related to plant lodging (Ennos, 1990;Kahn, 1985;Stoffella and Kahn, 1986;Stoffella et al, 1979a), flooding tolerance (Kahn et al, 1985), and nodule formation (Kahn and Stoffella, 1991). Zobel (1989) has reviewed studies on the effects of edaphic and environmental factors, such as moisture, temperature, mineral concentration, and gaseous atmosphere, on root morphology.…”
mentioning
confidence: 99%
“…Deeper roots probably provide greater anchorage within the subsoil, thereby lessening the amount of heaving damage. The force required to vertically extract agricultural crops from unfrozen soil varies with root size (Colette, 1962;Stoffella et al, 1979). Nikki (1953) has described different kinds of heaving injury as related to root morphology.…”
mentioning
confidence: 99%